Peran Order Taker Terhadap Kinerja Room Attendant di Hotel Shangri-La Jakarta - Peter Sava Dojo Mariano; Roy Daniel Samboh (LPPM and Travel Operation Department Universitas Asa Indonesia, 2025)
Shangri-La Jakarta is a 5-star hotel located in the center of Jakarta. Within a hotel, there are departments that have their own tasks, functions, and responsibilities. In the housekeeping department, there is a liaison between the housekeeping department and other departments, as well as guests. The order taker is the center of information about housekeeping and handles requests from guests and other departments to ensure the smooth running of the housekeeping department. The data collection methods used in this study include observation, interviews, documentation, and direct questionnaires with 20 room attendants at Shangri-La Jakarta Hotel regarding the role of the order taker in the performance of a room attendant at the hotel. Using the mean calculation technique, the result obtained was 4.79 points, indicating that the 20 staff members strongly agree that the role of the order taker significantly assists the performance of a room attendant at Shangri-La Jakarta Hotel. Keywords : housekeeping, departement, order taker, room attendant